Government Policy of Independent Learning-Independent Campus: Analysis of Student Knowledge and Readiness - Richardo Barry Astro; Konstantinus Denny Pareira Meke; Kristina Sara; Maria Adelvin Londa; Ferdinandus Lidang Witi (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aimed to analyze the knowledge and readiness of students in the application of Independent Learning-Independent Campus (MBKM) in the Study Program of Information Systems, Faculty of Information Technology, Flores University. This study applied a survey method with a descriptive approach. The data obtained from the population are 277 student respondents. The instrument used in this study was a questionnaire using SPADA DIKTI by the Ministry of Education, Culture, Research, and Technology (KEMDIKBUD RISTEK). Data that has been collected through questionnaires were analyzed using descriptive analysis. The results of this study indicated that students in the Study Program of Information Systems, Faculty of Information Technology, Flores University have sufficient knowledge and readiness and a positive response to the MBKM program. This shows that MBKM has a positive impact on the technical, learning process and evaluation of learning activities in higher education.